Municipal solid waste management and health risk implication in Zanzibar - Ally, Biubwa Faki (2015)
Solid waste is a visible concern in Zanzibar. One of the fundamental problems facing Zanzibar communities is the lack of formal system for solid waste management and is more apparent in informal settlements. It is estimated that, more than 50% of the diseases that affects people of Zanzibar are related to unsanitary environments which highly associated with poor waste management practices. The study aimed at assessing the current municipal waste practices and associated health risks in the municipality. Necessary data was obtained through interview administered questionnaire on one to one basis with a total of 200 households systematically selected from their residential areas. Similarly, photograph, documentation, field and direct observation were considered to add value of information. The results revealed that, more than half of respondents (66.5%) have access to collection services in their residence and 33.5% don‟t have any collection services. All residents in Zone A (N = 50) receive collection services followed by Zone B (N = 41) while residents in Zone C (13%) and Zone D (8%) don‟t have adequate collection services. Within the household, open containers such as plastic buckets (55%) and plastic sucks (32.5%) are usually used for the storage of waste and majority of respondents don‟t practice waste sorting in their homes (92%). The method of disposal is mainly communal collection containers (36.5%) including metal skips and slabs, through door to door collection service (25%) and indiscriminately disposal in open piles (29%). Burning or burying is common practices in the residential areas without access to collection services. There is low level of awareness about specific health and environmental problems associated with poor collection and disposal. Analysis revealed that there is significant relationship between household practices and reported health symptoms. The prevalence of respiratory illness, skin rashes, under 5 children diarrhea and malaria observed was higher in Zone C which is nearby the dumping site compared to other zones (A, B, and D). Reported health symptoms were more noticed to children aged 5-15 years particularly respiratory symptoms than other age category. The results depicted statistically significant relationship only between reported health symptoms and practices implying that improper waste management practices increase public health risks in terms of disease occurrence such as respiratory symptoms, diarrhea and other sanitation borne illness. Therefore, institutional capacity should be strengthened by moving it from centralized to decentralized approach. Also involvement of all stakeholders (government agencies, public, private and informal sectors; NGOs and CBOs) in system design from planning of MSWM issues to operations should be considered a synergy for effective and sustainable MSWM system in the Municipality.